ADAPTASI ARSITEKTUR TRADISIONAL RUMAH GAYO BERDASARKAN MEMORI KOLEKTIF - Yosantia, Muhammad Ferah; Dewi, Cut; Safwan (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2023)
The Gayo tribe is distinct in its language, clothes, ornamentation, culinary, and architectural works, all of which reflect the group's unique activities. The traditional Gayo communal house, known as Umah Gayo or Gayo House, is one example of originality. This paper aims to compare the adaptation of the Gayo traditional house to the surrounding environment based on literature with the community's collective memory, which has not been scientifically investigated. This study employs a qualitative technique with a descriptive approach to understand the Gayo traditional house's adaptability to its surroundings. Data was gathered through a literature review and direct observation of the remaining Gayo home structures. In addition, in-depth interviews with essential informants were undertaken. The findings reveal that the Gayo traditional house is a structure created by adapting to its surroundings, with the design, floor layout, and materials reflecting the rugged terrain of the Gayo area.